Beyond enlightenment : Buddhism, religion, modernity - Cohen, Richard S., 1963- (Routledge critical studies in Buddhism., 2006)
The vast majority of books on Buddhism describe the Buddha using the word enlightened, rather than awakened. This bias has resulted in Buddhism becoming generally perceived as the eponymous religion of enlightenment. Beyond Enlightenment is a sophisticated study of some of the underlying assumptions involved in the study of Buddhism (especially, but not exclusively, in the West). It investigates the tendency of most scholars to ground their study of Buddhism in these particular assumptions about the Buddha's enlightenment and a particular understanding of religion, wh.